A Tool to Quantify the Functional Impact of Oscillopsia - Anson, Eric R.; Gimmon, Yoav; Kiemel, Tim; Jeka, John J.; Carey, John P. (Frontiers in Neurology, 2018)
Background: Individuals with bilateral vestibular hypofunction (BVH) often report symptoms of oscillopsia during walking. Existing assessments of oscillopsia are limited to descriptions of severity and symptom frequency, neither of which provides a description of functional limitations attributed to oscillopsia. A novel questionnaire, the Oscillopsia Functional Impact scale (OFI) was developed to describe the impact of oscillopsia on daily life activities. Questions on the OFI ask how often individuals are able to execute specific activities considered to depend on gaze stability in an effort to link functional mobility impairments to oscillopsia for individuals with vestibular loss. Methods: Subjective reports of oscillopsia and balance confidence were recorded for 21 individuals with BVH and 48 healthy controls. Spearman correlation coefficients were calculated to determine the relationship between the OFI and oscillopsia visual analogue scale (OS VAS), oscillopsia severity questionnaire (OSQ), and Activities Specific Balance Confidence scale to demonstrate face validity. Chronbach’s α was calculated to determine internal validity for the items of the OFI. A one way MANOVA was conducted with planned post-hoc paired t-tests for group differences on all oscillopsia questionnaires using a corrected α = 0.0125. Results: The OFI was highly correlated with measures of oscillopsia severity (OS VAS; r = 0.69, p < 0.001) and frequency (OSQ; r = 0.84, p < 0.001) and also with the Activities Specific Balance Confidence scale (r = -0.84, p < 0.001). Chronbach’s α for the OFI was 0.97. Individuals with BVH scored worse on all measures of oscillopsia and balance confidence compared to healthy individuals (p’s < 0.001). Conclusions: The OFI appears to capture the construct of oscillopsia in the context of functional mobility. Combining with oscillopsia metrics that quantify severity and frequency allows for a more complete characterization of the impact of oscillopsia on an individual’s daily behavior. The OFI discriminated individuals with BVH from healthy individuals.